State of the worlds' indigenous peoples - United Nations. Department of Economic and Social Affairs; Permanent Forum on Indigenous Issues (United Nations).; United Nations. Statistical Division (New York United Nations, 2009)
One condition needed for facilitating the implementation of the United Nations Declaration on the Rights of Indigenous Peoples is information about those peoples. The chapters in this publication are based on the thematic areas within the mandate of the Permanent Forum on Indigenous Issues, and highlight some major issues indigenous peoples face--Foreword
Poverty and well-being -- Culture -- Environment -- Contemporary education -- Health -- Human rights -- Emerging issues.
ST/ESA/328
"United Nations publication. Sales no. 09.VI.13."--T.p. verso
Includes bibliographical references.
Keywords: Indigenous peoples -- Economic aspects; Indigenous peoples -- Social conditions; Minorities -- Economic aspects; Minorities -- Social conditions; Acculturation; Culture conflict